2006
DOI: 10.1186/1744-8603-2-6
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance as a global threat: Evidence from China, Kuwait and the United States

Abstract: Background: Antimicrobial resistance is an under-appreciated threat to public health in nations around the globe. With globalization booming, it is important to understand international patterns of resistance. If countries already experience similar patterns of resistance, it may be too late to worry about international spread. If large countries or groups of countries that are likely to leap ahead in their integration with the rest of the worldChina being the standout case -have high and distinctive patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
90
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(93 citation statements)
references
References 23 publications
2
90
1
Order By: Relevance
“…Decreased susceptibility was also found in Europe (1). In China, it was reported that the percentage of ciprofloxacin resistance rose from 2% in 1994 to 18% in 2000 (25). However, a higher percentage of ciprofloxacin resistance was found in this study.…”
contrasting
confidence: 54%
“…Decreased susceptibility was also found in Europe (1). In China, it was reported that the percentage of ciprofloxacin resistance rose from 2% in 1994 to 18% in 2000 (25). However, a higher percentage of ciprofloxacin resistance was found in this study.…”
contrasting
confidence: 54%
“…The high proportion of highly antimicrobial-resistant pneumococcal isolates recovered is consistent with common prior antibiotic use within the general area serviced by this hospital. Antibiotics are widely available without prescription in China (Yao et al, 2011;Zhang et al, 2006), so it is likely that antibiotic-susceptible strains were under-represented in our survey. It is also likely that many of the specimens were collected after antibiotics were given to the patients in the hospital.…”
mentioning
confidence: 99%
“…In the developing countries nowadays multiple antibiotic resistance have been observed among important pathogens viz., Escherichia coli; MRSA, VREF; Klebsiella; Vibrio etc (Bozdogan et al, 2003;Byarugaba, 2004;Soulsby, 2005;Zhang et al, 2006). Uncontrolled and widespread application of antibiotics in both human and veterinary medicines is equally responsible for increase in prevalence of antibiotic-resistant bacterial infections, and emergence of new antimicrobial resistant pathogenic strains of various infectious agents.…”
mentioning
confidence: 99%